Do financial development and institutional quality impede or stimulate the shadow economy? A comparative analysis of developed and developing countries - Waqar Ameer; Kazi Sohag; Qilin Zhan; Syed Hasanat Shah; Zhang Yongjia (Humanities & Social Sciences Communications)
Abstract Financial development (FD) and institutional quality (IQ) shape the invisible informal economies. This study conducts an empirical analysis of how financial development (FD) and institutional quality (IQ) impact the hidden shadow economy, with a particular focus on the differences between developed and developing countries. Using the CS-ARDL estimation technique, the findings reveal that FD and improved IQ significantly reduce the shadow economy in developing countries while these factors fuel the growth of the underground economy in developed nations. The study also illustrates that in developing nations, a synergy between economic growth, enhanced IQ, and advanced FD effectively contributes to shrinking the shadow economy. These empirical insights offer valuable policy implications, suggesting that adaptive strategies considering the stage of financial development and institutional quality can effectively mitigate the impact of the shadow economy.